Unveiling the Most Common Social Media Platforms Used for Marketing in Higher Education Institutions in Zambia - Mukosa, Francis; Kayombo, Kelvin Mukolo (RA Journal of Applied Research, 2022)
Social Media Marketing has become one of the most useful and popular means of marketing Higher Education Institutions (HEIs) globally. The main aim of this research was to investigate the most common Social Media platforms used in HEIs in Zambia and then determine the best combinations of Social Media platforms for marketing HEIs. The research used a structured questionnaire designed in Google forms to collect responses from 321 respondents which were analyzed in SPSS version 20 using descriptive analysis, Bivariate tools and QQ plots. The findings revealed that WhatsApp and Facebook are the most commonly used Social Media platforms in HEIs in Zambia. Additionally, the best combination of Social Media platforms for marketing HEIs are Facebook and Twitter followed by Twitter and WhatsApp. This research also brought out the findings that there is an association between Social Media platform signed up for and age range. The research brings out the best combination of Social Media platforms that professionals managing Social Media Marketing in HEIs can use to develop an effective Social Media Marketing mix.